Fiscal Reaction Function: Evidences from CESEE countries - Zdravković, Aleksandar; Zubović, Jovan; Bradić-Martinović, Aleksandra (Industrija, 2013)
The aim of this paper is to improve on the methodology set in previous attempts to estimate the impact of gross government debt to primary balances in a wide set of 21 CESEE countries. Since the result of the long-lasting crisis in those countries is rising imbalance of public finances it is necessary to analyze what factors are causing such effects. Running the fixed effect, pooled and GMM regression it was found that both lagged government debt and output gap are positively related to primary balance. Moreover there was found evidence of non-linear relationship between primary balance and lagged debt, with fiscal fatigue occurrence at 70% threshold. Estimation of the augmented model shows that countercyclical response of primary balance is more pronounced in economic downturn relative to boom in cycle.
Keywords: Government debt; CESEE; Fiscal reaction function